To the Lepidoptera fauna of Evenk District (Russia, East Siberia) - Svyatoslav A. Knyazev; Veronika G. Nikonova (Acta Biologica Sibirica, 2025)
The article contains a list of 47 species of Lepidoptera from the Thyrididae, Crambidae, Tortricidae, Hesperiidae, Papilionidae, Pieridae, Lycaenidae, Nymphalidae (including Satyrinae), Geometridae, Erebidae families from the territory of Evenkia. 18 species are new to the North Yenisei Region in Catalog of Lepidoptera of Russia, among them Thyris fenestrella (Scopoli, 1763), Chrysoteuchia culmella (Linnaeus, 1758), Crambus lathoniellus (Zincken, 1817), Epiblema simploniana (Duponchel, 1835), Grapholita compositella (Fabricius, 1775), Euphydryas intermedia (Ménétriés, 1859), Mellicta britomartis Assmann, 1847, Lomaspilis marginata (Linnaeus, 1758), Chiasmia clathrata (Linnaeus, 1758), Jodis putata (Linnaeus, 1758), Xanthorhoe deflorata (Erschoff, 1877), Xanthorhoe designata (Hufnagel, 1767), Mesoleuca albicillata (Linnaeus, 1758), Idaea pallidata ([Denis & Schiffermüller], 1775), Scopula immorata (Linnaeus, 1758), Polypogon tentacularia (Linnaeus, 1758), Phytometra viridata (Clerck, 1759), Callistege mi (Clerck, 1759).